Modified polyolefin resin as well as preparation method and application thereof

By grafting maleic anhydride and copolymerized maleic anhydride in the polyolefin resin and conducting efficient ring opening reaction with epoxy compounds, the modified polyolefin resin is solved, and the problem of insufficient binding force between engineering plastics and metals is achieved with high efficiency Improved bonding and material performance.

CN119391085AActive Publication Date: 2025-02-07ORINKO HIGH PERFORMANCE MATERIALS TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411705829.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-07
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

Thermoplastics, especially engineering plastics with higher hardness, have weak bonding forces with metals, making it difficult to achieve efficient bonding.

Method used

By grafting maleic anhydride and copolymerized maleic anhydride in a polyolefin resin and performing efficient ring opening reaction with epoxy compounds, a modified polyolefin resin is formed, and the modified resin is blended and extruded with a catalyst. The modified resin is combined with the matrix resin. Perform melt blending.

Benefits of technology

It significantly improves the bonding strength between engineering plastics and metals, ensures that the material surface is smooth and flawless, and enhances metal adhesion, thereby improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses modified polyolefin resin as well as a preparation method and application thereof. The modified polyolefin resin is prepared from the following components in percentage by mass: 90-98% of polyolefin, 1-10% of an epoxy compound and less than 1% of a catalyst, wherein the polyolefin is maleic anhydride grafted polyolefin or maleic anhydride copolymerized polyolefin. The invention provides brand-new polyolefin resin and a modification method thereof, and the bonding strength of the resin and metal is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyolefin resin modification, in particular to a modified polyolefin resin and a preparation method and application thereof. Background Art

[0002] Thermoplastics, especially engineering plastics with high hardness, usually have difficulty bonding with metals. On the one hand, the surface energy difference between plastics and metals is large. In particular, general-purpose plastics represented by polyolefins basically do not contain polar groups and have very weak bonding with metals. The bonding strength of other polar plastics such as nylon and polyester is also greatly different from that of conventional coatings. On the other hand, engineering plastics are hard and easy to crystallize, resulting in greater stress at the metal interface, making them easier to fall off during tearing.

[0003] Common methods to improve the bonding strength between thermoplastics and metals include: first, a series of surface treatments are performed on the metal end, such as applying primers and surface treatment agents to make the surface close to the surface energy of the plastic, and even forming a stronger covalent bond. However, the cost of treatment from the metal end is high; second, the plastic itself is made to contain polar monomers, such as maleic anhydride, vinyl acetate, etc., through copolymerization, or maleic anhydride or glycidyl ethers are grafted on the side groups of the plastic through free radical grafting to increase the polarity of the plastic itself, and then these modified polyolefin resins are added to ordinary resins to improve the bonding performance with metals. At present, the second improvement method generally needs to be improved. Summary of the invention

[0004] In view of this, the present invention provides a modified polyolefin resin and a preparation method and application thereof to solve the problems raised in the above background technology, provide a new polyolefin resin and a modification method thereof, and greatly improve the bonding strength between the resin and the metal.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention discloses a modified polyolefin resin, which is prepared from the following components in percentage by mass:

[0007] Polyolefin 90-98%,

[0008] Epoxide 1-10%,

[0009] Catalyst is less than 1%;

[0010] Wherein, the polyolefin is maleic anhydride grafted polyolefin or maleic anhydride copolymerized polyolefin.

[0011] As a further solution of the present invention: the main chain of the maleic anhydride grafted polyolefin is any one of a homopolymer or copolymer of ethylene, propylene, 1-butene, butadiene, 1-hexene, 1-octene, and styrene, and maleic anhydride is grafted on the polymer molecular chain.

[0012] As a further solution of the present invention: the maleic anhydride copolymerized polyolefin is obtained by copolymerizing maleic anhydride with ethylene or styrene.

[0013] As a further solution of the present invention: the melt index of the maleic anhydride grafted polyolefin is 200-1000 g / 10 min.

[0014] As a further solution of the present invention: the content of maleic anhydride in the maleic anhydride copolymerized polyolefin is greater than 50%.

[0015] As a further embodiment of the present invention: the epoxy compound is at least one of an epoxy resin and a mixture of multiple compounds with 1-2 epoxy groups; and / or,

[0016] The epoxy compound has an epoxide equivalent weight (EEW) of 500-3000 g / mol.

[0017] As a further solution of the present invention: the catalyst is a nitrogen-containing compound with a proton acceptor.

[0018] In a second aspect, the present invention discloses a method for preparing the modified polyolefin resin as described above, wherein each component is weighed according to mass percentage, mixed evenly and reacted and extruded at 150-300° C. to obtain the modified polyolefin resin.

[0019] In a third aspect, the present invention discloses an application of the modified polyolefin resin as described above, wherein the modified polyolefin resin is added to a base resin and mixed evenly to form a new modified resin; in the modified resin, the amount of the modified polyolefin resin is 1-30w%.

[0020] As a further solution of the present invention: the base resin is polypropylene or polyamide.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention combines polyolefin, epoxy compound and catalyst by means of co-extrusion, and immediately initiates chemical reaction during the extrusion process. Specifically, the process involves efficient ring-opening reaction between epoxy group and maleic anhydride under the catalysis of catalyst. Subsequently, maleic anhydride grafted polypropylene / maleic anhydride copolymerized polyolefin modified by chemical reaction is melt-blended with matrix resin. More importantly, since epoxy group has fully participated in the reaction with maleic anhydride during the extrusion stage, unintended local cross-linking between epoxy group and matrix resin is avoided in the subsequent melt-blending process. This improvement not only ensures that the surface of engineering plastic is smooth and flawless, significantly improves its appearance quality, but also enhances metal adhesion, thereby giving the material more superior performance. DETAILED DESCRIPTION

[0023] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0025] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0026] Resin 1: Maleic anhydride grafted polypropylene, OREVAC CA100, SK, Korea, maleic anhydride content>2%.

[0027] Resin 2; Ethylene-maleic anhydride copolymer, ZeMac E60, Vantreus, maleic anhydride content 78%

[0028] Epoxy compound 1: Epoxy resin E06, Baling Petrochemical, epoxy equivalent 1500-1800;

[0029] Epoxy compound 2: alkylene glycidyl ether, Jiangsu Maoyun, epoxy equivalent 235;

[0030] Catalyst: imidazole, Sinopharm;

[0031] Base resin 1: Polypropylene K4818, MI=23, Yanshan Petrochemical,

[0032] Matrix resin 2: PA1012 nylon, MI=5, Huitong new material.

[0033] All materials are commercially available conventional products.

[0034] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0035] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0036] The standards for the test items involved in the embodiments and comparative examples are as follows:

[0037] Melt index: standard reference GB / T 3682.1-2018, test conditions: 230℃, 2.16kg;

[0038] Adhesion: sandblast a 1cm wide Q235 steel sheet with 200 mesh quartz sand, then ultrasonically treat it with detergent solution for 10 minutes, finally scrub the sandblasted surface with acetone, spread the particles on the surface of the steel sheet, melt the particles on the surface of the steel sheet with a flat plate vulcanizer at about 220℃, and make the resin layer 0.5-2mm thick. After taking out the flat plate vulcanizer, naturally cool and solidify, remove all the resin on the side of the steel sheet and leave only the resin on the surface of the steel sheet. Then peel off the resin layer at the long end of the steel sheet with a blade, pull it apart for about 5cm, keep the plastic layer intact, and there is no gap on the edge, then clamp the pulled plastic layer and the peeled steel sheet in the two chucks of the stretching machine respectively, pull the coating apart at a speed of 5mm / min, and record the maximum value during the pulling process.

[0039] Surface smoothness: Use a single screw extruder to extrude the sheet at 180-220°C, and visually observe whether the surface is smooth, whether there are bulges or overall flatness problems. Mark the visual flatness on a scale of 1-10, with higher values ​​indicating higher flatness.

[0040] Example 1

[0041] (1) Weigh 980 g of polyolefin, 18 g of epoxy compound, and 2 g of catalyst, mix them evenly, and extrude them in a twin-screw extruder to obtain a modified polyolefin resin;

[0042] (2) The modified polyolefin resin obtained in step (1) is uniformly mixed with the base resin 1 at a mass ratio of 1:9, and melt-blended through a twin-screw extruder to obtain an engineering plastic 1.

[0043] The performance test of engineering plastic 1 showed that the melt index MI was 32 g / 10 min, the adhesion was 12 N, and the surface smoothness was 3.

[0044] Wherein, the operating parameters of the twin-screw extruder in step (1) are: the temperature of zone 1 is 120°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, the head temperature is 220°C, and the average residence time of the mixed material is 2 min; the operating parameters of the twin-screw extruder in step (2) are: the temperature of zone 1 is 160°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, and the head temperature is 220°C.

[0045] Example 2

[0046] (1) Weigh 950 g of polyolefin 1, 45 g of epoxy compound 2, and 5 g of catalyst, mix them evenly, and extrude them in a twin-screw extruder to obtain a modified polyolefin resin;

[0047] (2) The modified polyolefin resin obtained in step (1) is uniformly mixed with the base resin 1 at a mass ratio of 1:9, and melt-blended through a twin-screw extruder to obtain an engineering plastic 2.

[0048] The performance test of engineering plastic 2 showed that the melt index MI was 34 g / 10 min, the adhesion was 20 N, and the surface smoothness was 3.

[0049] Wherein, the operating parameters of the twin-screw extruder in step (1) are: the temperature of zone 1 is 120°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, the head temperature is 220°C, and the average residence time of the mixed material is 3 min; the operating parameters of the twin-screw extruder in step (2) are: the temperature of zone 1 is 160°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, and the head temperature is 220°C.

[0050] Example 3

[0051] (1) Weigh 950 g of polyolefin 1, 10 g of epoxy compound 1, 30 g of epoxy compound 2, and 3 g of catalyst, mix them evenly, and extrude them in a twin-screw extruder to obtain a modified polyolefin resin;

[0052] (2) The modified polyolefin resin obtained in step (1) and the base resin 1 are uniformly mixed in a mass ratio of 3:7, and melt-blended through a twin-screw extruder to obtain an engineering plastic 3.

[0053] The performance test of engineering plastic 3 showed that the melt index MI was 58 g / 10 min, the adhesion was 28 N, and the surface smoothness was 3.

[0054] Wherein, the operating parameters of the twin-screw extruder in step (1) are: the temperature of zone 1 is 120°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, the head temperature is 220°C, and the average residence time of the mixed material is 3 min; the operating parameters of the twin-screw extruder in step (2) are: the temperature of zone 1 is 160°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, and the head temperature is 220°C.

[0055] Example 4

[0056] (1) Weigh 980 g of polyolefin, 18 g of epoxy compound, and 2 g of catalyst, mix them evenly, and extrude them in a twin-screw extruder to obtain a modified polyolefin resin;

[0057] (2) The modified polyolefin resin obtained in step (1) and the base resin 2 are uniformly mixed in a mass ratio of 5:95, and melt-blended through a twin-screw extruder to obtain an engineering plastic 4.

[0058] The performance test of engineering plastic 4 showed that the melt index MI was 3 g / 10 min, the adhesion was 25 N, and the surface smoothness was 3.

[0059] Wherein, the operating parameters of the twin-screw extruder in step (1) are: the temperature of zone 1 is 120°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, the head temperature is 220°C, and the average residence time of the mixed material is 4 min; the operating parameters of the twin-screw extruder in step (2) are: the temperature of zone 1 is 160°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, and the head temperature is 220°C.

[0060] Example 5

[0061] (1) Weigh 980 g of polyolefin, 18 g of epoxy compound, and 2 g of catalyst, mix them evenly, and extrude them in a twin-screw extruder to obtain a modified polyolefin resin;

[0062] (2) The modified polyolefin resin obtained in step (1) and the base resin 2 are uniformly mixed in a mass ratio of 2:98, and melt-blended through a twin-screw extruder to obtain an engineering plastic 5.

[0063] The performance test of engineering plastic 5 showed that the melt index MI was 0.5 g / 10 min, the adhesion was >30 N, and the surface smoothness was 4.

[0064] Wherein, the operating parameters of the twin-screw extruder in step (1) are: the temperature of zone 1 is 120°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, the head temperature is 220°C, and the average residence time of the mixed material is 4 min; the operating parameters of the twin-screw extruder in step (2) are: the temperature of zone 1 is 160°C, the temperature of zone 2 is 190°C, the temperatures of the remaining zones are all 230°C, and the head temperature is 220°C.

[0065] Comparative Example 1

[0066] Polyolefin 1 and matrix resin 1 were uniformly mixed in a mass ratio of 1:9, and added into a twin-screw extruder for melt blending. The melt blending process parameters of the twin-screw extruder were the same as those in Example 1 to obtain engineering plastic 6. The melt index MI of engineering plastic 6 was measured to be 36 g / 10 min, the adhesion was 6 N, and the surface smoothness was 3.

[0067] Comparative Example 2

[0068] 950 g of polyolefin 1, 45 g of epoxy compound 2, 5 g of catalyst and 9 kg of base resin 1 were weighed, mixed evenly and then melt-blended directly through a twin-screw extruder. The melt-blending process parameters were the same as those in Example 2 to obtain engineering plastic 7. The melt index MI of engineering plastic 7 was measured to be 37 g / 10 min, the adhesion was 12 N and the surface smoothness was 3.

[0069] Comparative Example 3

[0070] 950 g of polyolefin 1, 10 g of epoxy compound 1, 30 g of epoxy compound 2, and 9 kg of matrix resin 1 were weighed, mixed evenly, and then melt-blended through a twin-screw extruder. The melt-blending process conditions were the same as those in Example 3 to obtain engineering plastic 8. The melt index MI of engineering plastic 8 was measured to be 70 g / 10 min, the adhesion was 25 N, the surface was rough, and the smoothness was 5.

[0071] Comparative Example 4

[0072] Weigh 500g of polyolefin 1 and 9.5kg of matrix resin 2 and mix them evenly, and melt blend them through a twin-screw extruder. The melt blending process conditions are the same as those in Example 4 to obtain engineering plastic 9. The melt index MI of engineering plastic 9 is measured to be 8g / 10min, the adhesion is 17N, and the surface smoothness is 6.

[0073] Comparative Example 5

[0074] Weigh 490g of polyolefin 1, 9g of epoxy compound 1, 1g of catalyst, and 9.5kg of base resin 2 and mix them evenly, and melt blend them through a twin-screw extruder. The melt blending process conditions are the same as those in Example 4 to obtain engineering plastic 10. The melt index MI of engineering plastic 10 is measured to be 1.5g / 10min, the adhesion is 20N, and the surface smoothness is 6.

[0075] Comparative Example 6

[0076] 178 g of polyolefin 2, 20 g of epoxy compound 1, 2 g of catalyst and 9.8 kg of base resin 2 were weighed and mixed evenly, and melt-blended through a twin-screw extruder. The melt-blending process conditions were the same as those in Example 5 to obtain engineering plastic 11. The melt index MI of engineering plastic 11 was measured to be 0.2 g / 10 min, the adhesion was 25 N, and the surface smoothness was 8.

[0077] By comparing Example 1 with Comparative Example 1, it can be seen that after adding the same amount of the modified polyolefin described in the present invention, the adhesion of the polypropylene substrate to the metal is significantly improved compared with the maleic anhydride grafted polypropylene, while the appearance does not change.

[0078] By comparing Example 2 with Comparative Example 2, it can be seen that by first reacting maleic anhydride grafted polypropylene with an epoxy compound and then adding it to the polypropylene substrate, the reaction between epoxy and maleic anhydride can be more complete; while adding the base resin to the reaction greatly reduces the possibility of the reaction, so the bonding effect is reduced.

[0079] By comparing Example 3 with Comparative Example 3, it can be seen that when the added proportion of the modified polyolefin resin is large, no appearance problems are found after the maleic anhydride grafted polypropylene is first reacted with the epoxy compound and then added to the polypropylene substrate, while the directly mixed product has the epoxy compound and the resin phase separation to form a rough surface.

[0080] By comparing Example 4 with Comparative Example 4, it can be seen that when adding modified polyolefin resin to nylon resin (base resin 2), if maleic anhydride grafted polypropylene is reacted with epoxy compound before adding, it has better bonding strength than adding maleic anhydride grafted polypropylene alone.

[0081] By comparing Example 4 with Comparative Example 5, it can be seen that since the nylon resin (base resin 2) reacts with epoxy during extrusion, the nylon will be partially cross-linked when it is directly extruded with the epoxy compound and nylon, resulting in roughness during extrusion. However, after the maleic anhydride grafted polypropylene reacts with the epoxy compound and then added to the nylon, the epoxy group has reacted completely, so it will not affect the appearance during extrusion, and the bonding strength is also better.

[0082] By comparing Example 5 with Comparative Example 6, it can be seen that the polyethylene copolymerized maleic anhydride reacted with the epoxy compound and then added to the matrix resin has a better appearance and bonding strength than directly blending it with the matrix resin.

[0083] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0084] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A modified polyolefin resin, characterized in that It is prepared from the following components in percentage by mass: Polyolefin 90-98%, Epoxide 1-10%, Catalyst is less than 1%; Wherein, the polyolefin is maleic anhydride grafted polyolefin or maleic anhydride copolymerized polyolefin.

2. The modified polyolefin resin according to claim 1, characterized in that The main chain of the maleic anhydride grafted polyolefin is any one of homopolymers or copolymers of ethylene, propylene, 1-butene, butadiene, 1-hexene, 1-octene and styrene, and maleic anhydride is grafted on the polymer molecular chain.

3. The modified polyolefin resin according to claim 1, characterized in that The maleic anhydride copolymerized polyolefin is obtained by copolymerizing maleic anhydride with ethylene or styrene.

4. The modified polyolefin resin according to claim 1 or 2, characterized in that The maleic anhydride grafted polyolefin has a melt index of 200-1000 g / 10 min.

5. The modified polyolefin resin according to claim 1 or 3, characterized in that: The content of maleic anhydride in the maleic anhydride copolymerized polyolefin is greater than 50%.

6. The modified polyolefin resin according to claim 1, characterized in that The epoxy compound is at least one of epoxy resin and a mixture of multiple compounds with 1-2 epoxy groups; and / or, The epoxy compound has an epoxide equivalent weight (EEW) of 500-3000 g / mol.

7. The modified polyolefin resin according to claim 1, characterized in that The catalyst is a nitrogen-containing compound with a proton acceptor.

8. A method for preparing a modified polyolefin resin as claimed in any one of claims 1 to 7, characterized in that: The components are weighed according to mass percentage, mixed evenly and reacted and extruded at 150-300°C to obtain the modified polyolefin resin.

9. Use of the modified polyolefin resin according to any one of claims 1 to 7, characterized in that: The modified polyolefin resin is added into the base resin and mixed evenly to form a new modified resin; in the modified resin, the amount of the modified polyolefin resin is 1-30w%.

10. The use according to claim 9, characterized in that: The base resin is polyolefin or polyamide.

Citation Information

Patent Citations

  • Cross-linking agent and preparation method and application thereof

    CN106496370A

  • Adhesive and method of bonding to rigid substrates

    CN110337354A

  • High-adhesion and cracking-resistant polyethylene powder as well as preparation method and application thereof

    CN115260842A

  • Method for producing metal member-resin member joined body, and film

    CN116635219A

  • Dynamic cross-linked polymer of high-energy-storage and self-healing electric tree and preparation method of dynamic cross-linked polymer

    CN117069879A